2005
DOI: 10.1534/genetics.104.040295
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Phosphonoacetic Acid

Abstract: A mutant allele (pol3-L612M) of the DNA polymerase ␦ gene in Saccharomyces cerevisiae that confers sensitivity to the antiviral drug phosphonoacetic acid (PAA) was constructed. We report that PAA-sensitivity tagging DNA polymerases is a useful method for selectively and reversibly inhibiting one type of DNA polymerase. Our initial studies reveal that replication by the L612M-DNA pol ␦ requires Rad27 flap endonuclease activity since the pol3-L612M strain is not viable in the absence of RAD27 function. The L612M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 54 publications
6
34
0
Order By: Relevance
“…The largest elevations were obtained for L612K (13-fold), L612G (17-fold), and L612N (37-fold), the increase for L612N being similar to that seen for the pol3-01 mutant lacking exonucleolytic proofreading (29-fold) (29,32,43). The increase for L612M (7-fold) is in accord with the 3.5-fold elevation recently reported (44). Interestingly, the increase in mutation rate was not strictly correlated with other phenotypic deficiencies.…”
Section: Leu 612 Mutant Strains Exhibited Varying Cell Cycle Defects supporting
confidence: 88%
See 1 more Smart Citation
“…The largest elevations were obtained for L612K (13-fold), L612G (17-fold), and L612N (37-fold), the increase for L612N being similar to that seen for the pol3-01 mutant lacking exonucleolytic proofreading (29-fold) (29,32,43). The increase for L612M (7-fold) is in accord with the 3.5-fold elevation recently reported (44). Interestingly, the increase in mutation rate was not strictly correlated with other phenotypic deficiencies.…”
Section: Leu 612 Mutant Strains Exhibited Varying Cell Cycle Defects supporting
confidence: 88%
“…Based on the relative replication proficiency and the predominance of base substitutions in the mutation spectrum (86%; Table 2), we hypothesized that the L612M mutator phenotype may reflect mainly errors made by the polymerase, rather than secondary mutagenic processes induced by defective replication. The recent work of Li et al (44), which was published as we completed this manuscript, sheds light on the function of the L612M polymerase. These authors also observed a mutator phenotype; the rate of forward mutation at CAN1 was elevated 3.5-fold, consistent with our results.…”
Section: Discussionmentioning
confidence: 78%
“…Many questions concerning the exact binding site of PFA have remained elusive, however, in part because poor expression levels of recombinant UL54 have precluded prior crystallographic investigation. Moreover, it is still unclear why PFA preferentially inhibits herpesviridae DNA polymerases, whereas other family B polymerases, such as RB69 DNA polymerase (gp43) or the replicative eukaryotic DNA polymerases ␦ or ⑀, are left unaffected by the drug (11).…”
mentioning
confidence: 99%
“…Contrary to the findings for UL30 and UL54 DNA polymerases, the gp43 enzyme is relatively resistant to foscarnet (10). Like all ␣-like DNA polymerases, the RB69 enzyme in binary complex with DNA adopts the open conformation for the fingers do- Replicative capacity of wild-type virus and two independent recombinant HCMV strains harboring mutation W780V in HFFs determined by the GLuc reporter-based assay.…”
Section: Discussionmentioning
confidence: 87%
“…Despite a high degree of similarity with the UL30 and UL54 DNA polymerases, the gp43 enzyme is relatively resistant to the broad-spectrum antiviral agent foscarnet (10). It was suggested that the binding site for foscarnet on the UL54 DNA polymerase is located in close proximity to the ␥ phosphate of the bound nucleotide (11).…”
mentioning
confidence: 99%